Changes in the soil chemical characteristics of a coastal sandy soil as influenced by agroforestry and organic amendment. - Abu Bakar, Rosenani; Saad, Azizah; Hashim, Azizah; Ab. Shukor, Nor Aini (1994)
A field trial was conducted on a coastal sandy soil called BRIS soil (<3% silt and clay and can have a spodic horizon) to evaluate the use of agroforestry and organic amendment as appropriate practices in utilizing the land for agriculture. The trial was set up on a site consisting of three soil series,Rudua,Rhu Tapai and Malawi. Two types of organic fertilizers (POME : palm oil mill effluent,and Biopost : plant residue manure) were tested,without mycorrhiza. A fruit tree species,soursop,was planted and a short term crop grown in between the trees. The pH of the soil was 4.1-5.0. After 2 applications of organic fertilizer in 14 months there was a slight increase in soil pH to up to 5.9 in the Rudua and Rhu Tapai soils. However,the pH of the Malawi soil remained unchanged. The monsoon in this area,from October to January,prevented the organic materials to remain longer in the soil. At 4 months after the first applications of organic fertilizer,the % total N in the soil had increased up to 60cm depth but then decreased to the initial level after the monsoon period. It increased again slightly after the second application of organic fertilizer in May 1993. The organic carbon also increased from 0.81 - 0.98% to 1.17 - 2.77% in the top soil after the first application but decreased to the initial level even after the second application,except for the Malawi soil. The cation exchange capacity and exchangeable cations (Ca,Mg and K) in Rudua,Rhu Tapai and Malawi soils had increased greatly with both the POME and Biopost applications. Organic amendment of this coastal soil was found to be important in improving the soil fertility status in general.